Nomenclatural and taxonomic changes in parasitic isopods (Isopoda: Epicaridea), including two new families and note on the questionable association between monogeneans and bopyrids - Boyko, Christopher B.; Williams, Jason D. (Zootaxa, 2023)
Several long-standing taxonomic and nomenclatural problems in bopyroid and cryptoniscoid isopods are addressed. Within Bopyroidea we propose five new synonomies, three new combinations, a correction of the spelling of one species and a replacement name for another. In addition, the likely erroneous conclusion that a monogenean is an associate of bopyrids is discussed. Within Cryptoniscoidea, we determined the familial placement of three genera that were previously designated as incertae sedis (Capitoniscus Bourdon, 1972 and Carocryptus Schultz, 1977) or of doubtful affiliation (Cumoechus Hansen, 1916). In total, five species of cryptoniscoids are placed into two new families (Capitoniscidae n. fam. and Cumoechidae n. fam.), each containing at least one species known from both female and cryptoniscus larvae/paedomorphic male stages. Finally, the status of two cryptoniscoid genera is addressed: Gorgoniscus Grygier, 1981 is placed in Hemioniscidae, and Leponiscus Giard, 1887, is synonymized with Hemioniscus Buccholz, 1866.